Efeito da transposição de galharia sobre a fauna de artrópodes da serapilheira, em uma área de cerrado - Vergílio, Paula Cristina Benetton [UNESP]; Knoll, Fátima do Rosário Naschenveng [UNESP]; Mariano, Daniela da Silva; Dinardi, Nágila Maiara [UNESP]; Ueda, Marcos Yukio; Cavassan, Osmar [UNESP] (FapUNIFESP (SciELO), 2013)
The results of ecological restoration techniques can be monitored through biological indicators of soil quality such as the leaf litter arthropod fauna. This study aimed to determine the immediate effect of brushwood transposition transferred from an area of native vegetation to a disturbed area, on the leaf litter arthropod fauna in a degraded cerrado area. The arthropod fauna of four areas was compared: a degraded area with signal grass, two experimental brushwood transposition areas, with and without castor oil plants, and an area of native cerrado. In total, 7,660 individuals belonging to 23 taxa were sampled. Acari and Collembola were the most abundant taxa in all studied areas, followed by Coleoptera, Diptera, Hemiptera, Hymenoptera, and Symphyla. The brushwood transposition area without castor oil plants had the lowest abundance and dominance and the highest diversity of all areas, providing evidence of changes in the soil community. Conversely, the results showed that the presence of castor oil plants hampered early succession, negatively affecting ecological restoration in this area.
Effect of brushwood transposition on the leaf litter arthropod fauna in a cerrado area
Keywords: Acari; Collembola; Ecological restoration; Mesofauna; Signal grass